Hepatitis E Virus RNA Presence in Wild Boar Carcasses at Slaughterhouses in Italy - Mario Forzan; Maria Irene Pacini; Marcello Periccioli; Maurizio Mazzei (Animals, 2021)
Hepatitis E virus (HEV) is a waterborne and foodborne pathogen largely spread around the world. HEV is responsible for acute hepatitis in humans and it is also diffused in domestic and wild animals. In particular, domestic pigs represent the main reservoir of the infection and particular attention should be paid to the consumption of raw and undercooked meat as a possible zoonotic vehicle of the pathogen. Several studies have reported the presence of HEV in wild boar circulating in European countries with similar prevalence rates. In this study, we evaluated the occurrence of HEV in wild boar hunted in specific areas of Tuscany. Sampling was performed by collecting liver samples and also by swabbing the carcasses at the slaughterhouses following hunting activities. Our data indicated that 8/67 (12%) of liver samples and 4/67 (6%) of swabs were positive for HEV RNA. The presence of HEV genome on swabs indicates the possible cross-contamination of carcass surfaces during slaughtering procedures. Altogether, our data indicated that it is essential to promote health education programmes for hunters and consumers to limit the diffusion of the pathogen to humans.